Cardiotoxicity in Breast Cancer Treatment: What About Left Ventricular Diastolic Function and Left Atrial Function? - Timóteo, AT (2019)
Aims: Cardiotoxicity is a possible complication of cancer treatment, particularly with anthracyclines and anti-HER2 drugs. Systolic dysfunction has already been described. Diastolic dysfunction and left atrial function are less studied. We sought to analyze the impact of cardiotoxic treatments on left ventricular diastolic function and left atrial (LA) function. Methods and results: Retrospective study of 100 patients (all women, with a mean age of 54 ± 12 years) with three exams in the span of 1 year during treatment for breast cancer. Patients with previous cancer treatment, coronary artery disease, significant valvular disease, and atrial arrhythmias were excluded. Diastolic dysfunction was classified according to international guidelines and left atrial strain was analyzed by two-dimensional speckle tracking. In our sample, 74% received anthracyclines, 83% anti-HER2, and 76% radiation treatment. In the follow-up, 20% developed new or worsening diastolic dysfunction. Age was the only independent predictor (OR 1.93, 95% CI 1.04-3.58, P = .037). In left atrial function, only the contractile function was significantly reduced in 20.8% of the patients and age was also the only independent predictor, but with a protective effect (OR 0.51, 95% CI 0.28-0.91, P = .023). Conclusions: During breast cancer treatment, 20% of the patients develop new or worsening diastolic dysfunction, being age the main determinant, suggesting higher impact of chemotherapy in older patients. Contractile left atrial function is also compromised but, in this case, age seems to be protective. Our results support a stricter surveillance in older patients together to eventually adjust chemotherapy regimens.